Bio-based repairable high-conductivity high-sensitivity sensing fiber as well as preparation and application thereof
Flexible fibers with core-shell structures are constructed by using silk fibroin/chitin nanocrystal composites and microfluidic spinning technology, which solves the sustainability problem of traditional materials in stress environments, achieves high conductivity and efficient self-repair, and is suitable for wearable sensors and implantable medical devices.
Patent Information
- Application Number
- CN202510836923.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-22
- Publication Date
- 2025-09-26
AI Technical Summary
Existing flexible sensor materials have poor sustainability in complex stress environments. Traditional conductive materials are easy to break, carbon-based materials have high interface resistance and limited flexibility, and their self-healing ability is insufficient, making it difficult to meet high-precision sensing requirements.
Using silk fibroin/chitin nanocrystal composite materials, a core-shell structure is constructed through coaxial microfluidic spinning technology to form an ion-electron dual-conducting network. Efficient self-repair is achieved by utilizing multiple hydrogen bonds and metal coordination bonds, and an electronic conduction network is formed by combining with functionalized graphene.
The flexible fiber has high conductivity and efficient self-healing ability, with an electrical conductivity of 48 S/m, a self-healing efficiency of more than 90%, and a mechanical strength of more than 5 MPa, making it suitable for wearable sensors and implantable medical devices.
Smart Images

Figure CN120700610A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible electronic materials and devices, and specifically relates to a bio-based repairable highly conductive and highly sensitive sensing fiber and its preparation and application. Background Art
[0002] Flexible electronics technology has been developing rapidly in recent years, with many renowned research institutions and scholars both domestically and internationally continuously researching and improving the materials, structures, and fabrication processes of flexible sensors. Flexible, wearable, and stretchable electronic devices, with their advantages of being thin, lightweight, flexible, stretchable, consistent, and compatible, are increasingly in demand in areas such as human-computer interaction, health monitoring, and soft robotics.
[0003] However, most traditional materials with excellent electronic properties have poor sustainability in complex stress environments, making them difficult to directly incorporate into flexible and stretchable device structures. For example, traditional conductive materials are rigid, easily broken, and non-stretchable; carbon-based materials have high interfacial resistance, limited flexibility / stretchability, and their self-healing capabilities fall short of the requirements for flexible electronic skin; and existing conventional conductive hydrogels are prone to water loss, easily destroying their conductive networks, and exhibiting insufficient conductivity (<1 S / m), making them difficult to meet high-precision sensing requirements.
[0004] Bio-based materials are abundant, renewable, biocompatible, and biodegradable. For example, patent CN114456581A prepares a conductive sodium alginate fiber, which relies on ionic conductivity, has low conductivity, and is prone to water loss and failure. US20220002780A1 prepares a PEDOT:PSS / gelatin composite fiber, but fails to resolve the mechanical-self-healing contradiction and results in low repair efficiency (<70%).
[0005] Therefore, this field urgently needs to develop a gel fiber with both high conductivity and efficient self-repairing ability. The key lies in how to form a stable and high-density conductive structure in a bio-based matrix and establish an efficient self-repairing mechanism. Summary of the Invention
[0006] To address the aforementioned shortcomings and deficiencies in the existing technology, the present invention provides a bio-based, repairable, highly conductive, and highly sensitive sensing fiber, as well as its preparation and application. The gel fiber prepared by the present invention exhibits bio-based, self-repairing, high conductivity, and flexibility and stretchability, making it suitable for applications such as wearable sensors, implantable medical devices, and human-computer interfaces.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a bio-based repairable highly conductive and highly sensitive fiber comprises the following steps: (1) Preparation of core layer solution: silk fibroin solution, chitin nanocrystal dispersion and low-concentration electrolyte solution; (2) Preparation of shell solution: Add conductive filler and high-concentration electrolyte solution to silk fibroin solution; (3) The core layer and the shell layer are co-extruded through a coaxial microfluidic spinning device, and the fibers are placed in a calcium chloride aqueous solution coagulation bath for in-situ crosslinking. Then, they are stretched, oriented, and steam annealed to obtain core-shell structured fibers, i.e., bio-based, repairable, highly conductive, and highly sensitive fibers.
[0008] Preferably, the concentration of the silk fibroin solution (SF) is 15 wt %, the concentration of the chitin nanocrystal dispersion (ChNCs) is 2 wt %, the high concentration electrolyte solution (HCE) is 1.5 M, the low concentration electrolyte solution (LCE) is 0.5 M, and the concentration of the conductive filler (CF) is 20 wt %; The mass ratio of each component is: a. Shell solution: SF: ChNCs: HCE = 70:20:10; b. Nuclear layer solution: SF: CF: LCE = 80:15:5.
[0009] Preferably, the electrolyte is selected from one of CaCl2 and ZnCl2.
[0010] Preferably, the silk fibroin is purified silk fibroin.
[0011] More preferably, the purification includes degumming, washing, dissolution with lithium bromide solution and dialysis.
[0012] Preferably, the chitosan nanocrystal dispersion is prepared by the following method: a. Acid hydrolysis: dry cellulose raw material (such as cotton linter) is added The solution was stirred vigorously for 30-90 min (the reaction time affected the size and yield of ChNCs); b. Termination and washing: Pour the reaction solution into 10 times the volume of ice water to terminate the reaction. After settling, remove the supernatant and centrifuge or dialyze repeatedly until the supernatant or dialyzed solution is neutral and free of (Available solution testing); c. Dispersion and homogenization: The washed ChNCs precipitate is dispersed in an appropriate amount of deionized water to obtain a translucent or milky white, stable ChNCs aqueous dispersion.
[0013] Preferably, the conductive filler is functionalized reduced graphene oxide.
[0014] More preferably, the functionalized reduced graphene oxide is prepared by the following method: a. Raw material preparation: graphene oxide (GO) Using natural flake graphite (particle size 20–50 μm) as raw material, the modified Hummers method was used: At a low temperature of 0–35°C, graphite is mixed with 98% concentrated (Use 50 mL / g graphite) mix and slowly add (Mass ratio :graphite = 6:1); the temperature was raised to 98°C and reacted for 2–12 hours to generate GO containing epoxy, hydroxyl, and carboxyl groups.
[0015] b. Functionalization GO was dispersed in toluene (concentration 2 mg / mL), and the functionalizing reagent 3-aminopropyltrimethoxysilane (APS) was added (mass ratio APS:GO = 1:5); the reaction was carried out at 80–90°C for 24 h to obtain APS-grafted functionalized graphene oxide (FGO).
[0016] c. Purification After the reaction is completed, repeated centrifugation, dialysis or filtration are performed to remove unreacted functionalization reagents, by-products and solvents to obtain a pure functionalized graphene oxide (FGO) dispersion.
[0017] d. Restore Mix the functionalized graphene oxide (FGO) dispersion with excess 57% concentrated HI acid. Ensure that the FGO is fully soaked with HI. Under the protection of a molten salt, heat to 80-100°C and maintain the reaction at this temperature for 1-2 hours. After the reaction is complete, cool the mixture to room temperature. Slowly pour it into a large amount of deionized water to dilute it. Filter the solid product, repeatedly wash it, and dry it to obtain the reduced functionalized graphene material (rFGO).
[0018] Preferably, the microfluidic flow rate is 0.5-2 mL / h for the core layer and 1-4 mL / h for the shell layer; the cross-linking time is 10-30 min.
[0019] Preferably, the draw ratio of the stretching orientation is 1:1-1.5, and the temperature of the steam annealing treatment is 50-70°C.
[0020] The present invention also provides a bio-based repairable high-conductivity and high-sensitivity sensing fiber prepared by the above preparation method.
[0021] Preferably, the diameter of the fiber is 50-200 μm.
[0022] The present invention also provides the use of the bio-based repairable highly conductive and highly sensitive sensing fiber in wearable sensors, implantable medical devices or human-computer interaction interfaces.
[0023] The bio-based, repairable, highly conductive, and highly sensitive fiber of the present invention is a silk fibroin / chitin nanocrystal (SF / ChNC) composite ion-electronic dual-conducting self-healing hydrogel fiber, which achieves performance breakthroughs through a triple synergistic effect: (1) Bio-based reinforced skeleton: recombinant silk fibroin (SF) as the matrix and chitin nanocrystals (ChNCs) as dynamic crosslinkers, providing high toughness (tensile strength > 5 MPa) and multiple hydrogen bonds / coordination bonds repair network; (2) Dual-channel conduction: Ion pathways: Electrolytes build fast ion migration channels; Electronic pathway: Functionalized graphene (rGO) forms an electronic conduction network; (3) Core-shell fiber structure: Heterogeneous integration of “conductive core + repair shell” is achieved through microfluidic spinning, protecting the conductive network and improving the repair efficiency (>90%). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the cross-sectional structure of core-shell fibers (core: electronic conductor network; shell: ChNCs cross-linked network); Figure 2 Self-healing mechanism diagram (multiple hydrogen bonds coordination bond reorganization process). DETAILED DESCRIPTION
[0025] In order to make the technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] Example 1:
[0027] like Figure 1 As shown, this embodiment prepares a system using silk fibroin as a matrix, chitin nanocrystals (ChNCs) as a dynamic crosslinker, and an ion conductor ( ) and electronic conductor (rGO), and constructed ion-electron dual-conducting networks and core-shell structures through microfluidic spinning.
[0028] The preparation method of this embodiment comprises the following steps: 1. Purification of silk fibroin: a. Degumming: Chop the silk fibers into small pieces and add them to a boiling sodium carbonate solution according to the size of the silk fibers. Boil for 30-60 minutes. Repeat 2-3 times until the solution is no longer turbid. b. Cleaning: Rinse the degummed silk fibers repeatedly with plenty of deionized water and use pH test paper to determine the acidity and alkalinity of the cleaning solution. Stop cleaning when the cleaning solution is neutral. c. Dissolution dialysis: Add the washed SF fiber to the LiBr solution and stir continuously for 1-4 hours; place it in a dialysis bag and dialyze it in continuously flowing deionized water for 3 days (change the water several times a day) to completely remove LiBr and small molecular impurities. The dialysis endpoint can be determined by measuring the conductivity of the dialysate or Solution detection Br⁻ Ion confirmation.
[0029] 2. Preparation of Chitosan Nanocrystal Dispersion: a. Acid hydrolysis: Add dry cotton wool The solution was stirred vigorously for 60 minutes; b. Termination and washing: Pour the reaction solution into 10 times the volume of ice water to terminate the reaction. After settling, discard the supernatant. Repeated centrifugation or dialysis until the supernatant or dialyzed liquid is neutral and free of ; c. Dispersion and homogenization: The washed ChNCs precipitate was dispersed in an appropriate amount of deionized water to obtain a milky white, stable ChNCs aqueous dispersion.
[0030] 3. Preparation of functionalized reduced graphene oxide: a. Raw material preparation: graphene oxide (GO) Using natural flake graphite (particle size 20–50 μm) as raw material, the modified Hummers method was used: At a low temperature of 0–35°C, graphite is mixed with 98% concentrated (Use 50 mL / g graphite) mix and slowly add (Mass ratio :graphite = 6:1); the temperature was raised to 98°C and reacted for 2–12 hours to generate GO containing epoxy, hydroxyl, and carboxyl groups.
[0031] b. Functionalization GO was dispersed in toluene (concentration 2 mg / mL), and the functionalizing reagent 3-aminopropyltrimethoxysilane (APS) was added (mass ratio APS:GO = 1:5); the reaction was carried out at 80–90°C for 24 h to obtain APS-grafted functionalized graphene oxide (FGO).
[0032] c. Purification After the reaction is completed, repeated centrifugation, dialysis or filtration are performed to remove unreacted functionalization reagents, by-products and solvents to obtain a pure functionalized graphene oxide (FGO) dispersion.
[0033] d. Restore Mix the functionalized graphene oxide (FGO) dispersion with excess 57% concentrated HI acid. Ensure that the FGO is fully soaked with HI. Under the protection of a molten salt, heat to 80-100°C and maintain the reaction at this temperature for 1-2 hours. After the reaction is complete, cool the mixture to room temperature. Slowly pour it into a large amount of deionized water to dilute it. Filter the solid product, repeatedly wash it, and dry it to obtain the reduced functionalized graphene material (rFGO).
[0034] 4. Preparation of bio-based repairable highly conductive and sensitive sensing fibers a. Shell solution preparation: Add 15wt% chitin nanocrystals and 0.5M zinc chloride solution to the recombinant silk fibroin solution (mass ratio: SF: ChNCs: 1.5 = 70 : 20 : 10).
[0035] b. Preparation of core layer solution: Add 20wt% functionalized reduced graphene oxide (rGO) and 1.5M zinc chloride solution (mass ratio: SF: rGO: 0.5) to the recombinant silk fibroin solution. = 80 : 15 : 5); like Figure 2 As shown, a dual dynamic bonding network is formed inside the material: multiple hydrogen bonds and metal coordination bonds ( ), the synergistic effect of these two bonds enables the fiber to achieve efficient self-repair.
[0036] c. The fibers were coextruded through a coaxial microfluidic spinning device (inner diameter 200 μm / outer diameter 400 μm) at flow rates of 1.2 mL / h for the core layer and 2.5 mL / h for the shell layer. The fibers were then placed in a 2 wt% calcium chloride aqueous solution coagulation bath for in situ crosslinking for 15 minutes. The fibers were then stretched (draw-down ratio 1:1.2) and steam annealed at 60°C to obtain core-shell structured fibers.
[0037] 5. Test results of bio-based repairable highly conductive and sensitive fibers The fiber has an electrical conductivity of 48 S / m, and after being cut and placed in an environment of 25°C and 60% relative humidity for 30 minutes, the conductivity recovery rate reaches 95%. The mechanical strength is 8.6 MPa (>5 MPa).
[0038] Comparative Example 1: No dynamic crosslinker (ChNCs missing) Directly mixed with silk fibroin matrix Homogeneous fibers were prepared by combining electrolyte and rGO and cross-linking in an ethanol coagulation bath. Due to the lack of the dynamic hydrogen-bonding / coordination-bonding repair network constructed by chitin nanocrystals (ChNCs), the fiber self-healing efficiency was significantly reduced to 45% (30 minutes), and the mechanical strength was only 2.1 MPa, significantly lower than the >5 MPa of the present invention, demonstrating the key role of ChNCs in self-healing and mechanical strength.
[0039] Comparative Example 2: Single Ion Conductivity (No Electronic Conductor) Homogeneous fibers were prepared using only silk fibroin / ChNCs and electrolytes, without the introduction of an electronic conductor. The resulting conductivity was as low as 0.8 S / m, far below the invention's requirement of >5 S / m. The ionic conductive network easily broke and could not be recovered under high strain, leading to unstable sensing signals. This highlights the necessity of a synergistic ionic-electronic dual channel for high conductivity and stability.
[0040] Comparative Example 3: Homogeneous structure (no core-shell design) Silk fibroin / ChNCs, rGO, and electrolyte were homogenously mixed and spun. Despite a conductivity of 22 S / m, the self-healing efficiency was only 72% (30 minutes) because the conductive filler hindered dynamic bond recombination. Furthermore, the conductivity was lower than the 48 S / m of the core-shell structure, demonstrating that the homogenous design could not achieve the synergistic effect of "high-concentration conductive core + healing shell."
[0041] Comparative Example 4: Traditional chemical crosslinkers replacing ChNCs Glutaraldehyde was used instead of ChNCs to crosslink silk fibroin, and rGO and electrolytes were added. Covalent crosslinking completely lost the fibers' self-healing ability, and residual glutaraldehyde deteriorated their biocompatibility (cell viability <70%), reversibly validating the biocompatibility and reversible repair advantages of ChNCs' dynamic bonds.
[0042] Comparative Example 5: Ordinary blend spinning (non-microfluidic process) The core-shell components (SF / ChNCs shell + SF / rGO core) were prepared by conventional twin-screw extrusion and co-spinning, without in-situ crosslinking in a coagulation bath. Inadequate process precision resulted in a fuzzy and delaminated core-shell interface, reducing the conductivity to 12 S / m (compared to 48 S / m for microfluidic core-shell), demonstrating the irreplaceable role of microfluidic technology in the precise construction of heterogeneous structures.
[0043] The above comparative example system covers four dimensions: material composition (ChNCs / lack of electronic conductor), conductive mechanism (single ion path), structural design (homogenization limitation) and preparation process (non-microfluidic). The defect data reversely verifies the breakthrough advantages of the present invention in dynamic cross-linking network, dual-conductor synergy, core-shell heterogeneous integration and microfluidic precision molding.
[0044] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, based on the ideas provided by the present invention, there may be changes in the specific implementation methods, and these changes should also be considered as the scope of protection of the present invention.
Claims
1. A method for preparing a bio-based repairable high-conductivity and high-sensitivity fiber, characterized in that: The following steps are involved: (1) Preparation of core layer solution: silk fibroin solution, chitin nanocrystal dispersion and low-concentration electrolyte solution; (2) Preparation of shell solution: Add conductive filler and high-concentration electrolyte solution to silk fibroin solution; (3) The core layer and the shell layer are co-extruded through a coaxial microfluidic spinning device, and the fibers are placed in a calcium chloride aqueous solution coagulation bath for in-situ crosslinking. Then, they are stretched, oriented, and steam annealed to obtain core-shell structured fibers, i.e., bio-based, repairable, highly conductive, and highly sensitive fibers.
2. The preparation method according to claim 1, wherein The concentration of the silk fibroin solution (SF) was 15 wt %, the concentration of the chitin nanocrystal dispersion (ChNCs) was 2 wt %, the high concentration electrolyte solution (HCE) was 1.5 M, the low concentration electrolyte solution (LCE) was 0.5 M, and the concentration of the conductive filler (CF) was 20 wt %.
3. The preparation method according to claim 1, characterized in that The mass ratio of each component is: a. Shell solution: SF: ChNCs: HCE = 70:20:10; b. Nuclear layer solution: SF: CF: LCE = 80:15:
5.
4. The preparation method according to claim 1, characterized in that The electrolyte is selected from one of CaCl2 and ZnCl2.
5. The preparation method according to claim 1, characterized in that The silk fibroin is purified silk fibroin.
6. The preparation method according to claim 1, characterized in that The chitosan nanocrystal dispersion is prepared by the following method: a. Acid hydrolysis: Add the dry cellulose raw material to The solution was stirred vigorously for 30-90 minutes; b. Termination and washing: Pour the reaction solution into 10 times the volume of ice water to terminate the reaction. After settling, remove the supernatant and centrifuge or dialyze repeatedly until the supernatant or dialyzed liquid is neutral and free of ; c. Dispersion and homogenization: The washed ChNCs precipitate is dispersed in an appropriate amount of deionized water to obtain a translucent or milky white, stable ChNCs aqueous dispersion.
7. The preparation method according to claim 1, characterized in that The conductive filler is functionalized reduced graphene oxide.
8. The preparation method according to claim 1, wherein The microfluidic flow rate is 0.5-2 mL / h for the core layer and 1-4 mL / h for the shell layer; the crosslinking time is 10-30 min; the draw ratio of the stretching orientation is 1:1-1.5, and the temperature of the steam annealing treatment is 50-70°C.
9. A bio-based repairable, highly conductive, and highly sensitive fiber produced by the method according to any one of claims 1 to 8.
10. Use of the bio-based repairable highly conductive and highly sensitive sensing fiber according to claim 9 in wearable sensors, implantable medical devices or human-computer interaction interfaces.
Citation Information
Patent Citations
Use of aptamers in proteomics
US20220002780A1